Synthesis, structural characterization, and density functional theory calculations of the two new Zn (II) complexes as antibacterial and anticancer agents with a neutral flexible tetradentate pyrazole‐based ligand. (22nd January 2021) - Beheshti, Azizollah; Bahrani‐Pour, Maryam; Kolahi, Maryam; Shakerzadeh, Ehsan; Motamedi, Hossein; Mayer, Peter
Abstract : Two new mono‐ and dinuclear zinc (II) complexes with a formula of [Zn (L N )OMeCl] (1) and [Zn 2 (L N )(N 3 ) 2 Cl 2 ] (2) [where LN = 1, 1, 3, 3‐tetrakis(3, 5‐dimethyl‐1‐pyrazolyl)propane)] have been synthesized in methanol as a solvent and fully characterized by the single crystal X‐ray diffraction, elemental analysis, FT‐IR, UV–Vis, density functional theory (DFT) calculations, antibacterial, and anticancer properties. In both of them, zinc ion is tetrahedrally coordinated to two nitrogen atoms from one of the chelating bidentate bis(3, 5‐dimethylpyrazolyl)methane units of the LN ligand and one terminal chlorine. The forth coordination site was occupied by methoxy group in 1 and azide co‐ligand in complex 2 . In contrast to 1, in the structure of 2 two metal centers are bridged by the tetradentate chelating LN ligand to form a dinuclear complex. Interestingly, the environment around the central atom in these complexes are mimicked with the core structure of the zinc metalloproteinases, Thermolysin [NNO]ZnX and Carbonic anhydrase [NNN]ZnX for complexes 1 and 2, respectively. Data analysis of the antibacterial activities demonstrated that the gram positive species showed more sensitivity toward the target title agents. Although, both complexes exhibit antibacterial activities and kill bacteria at low concentration, but complex 1 has higher DNA cleavage activity than 2 . Additionally, the cytotoxicity of the free ligand and its complexes was evaluated against the human carcinoma cell line (Caco‐2) by the MTT method and the IC50 values were calculated for all of them. Due to the presence of pyrazole rings in the structure of the ligand and its complexes, these materials have a substantial potential to inhibit cancer cell metastasis. The energetic stabilization due to donor‐acceptor interactions in terms of the natural bond orbital (NBO) analyses and nonlinear optical properties were also examined by using the DFT calculations. Abstract : In the considered monomeric and dinuclear compounds, the zinc atoms are tetrahedrally coordinated . These complexes have a good potential against selected bacteria and cancer cells. Their density functional theory (DFT) calculations described the factors which involved in their stability.